An assessment of effective drug procurement in District Hospitals (a case study of Kwahu Government Hospital) - Sarpong, Patrick Boateng (2014)
A thesis submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of